Pharmacist intervention amid the coronavirus disease 2019 (COVID-19) pandemic: from direct patient care to telemedicine - Ali Elbeddini; Aniko Yeats (Journal of Pharmaceutical Policy and Practice, 2020)
Introduction The coronavirus disease (COVID-19) pandemic has placed enormous pressures on the Canadian healthcare system. Patients are expected to stay home in order to contain the spread of the virus, but understandably have numerous questions and concerns about their health. With physical distancing being of utmost importance during the pandemic, much of healthcare has been forced to move online or over the telephone. Virtual healthcare, in the form of video calls, email, or telephone calls with patients, can significantly enhance access to healthcare. Many clinics have moved their appointments online, and physicians are seeing their patients by means of online video calls. Similarly, patients are refilling their prescriptions online and calling pharmacists whenever they have questions about their medications or medical conditions. Pharmacists are considered the most accessible primary care providers, so it is crucial for patients to know that pharmacists are there to support them throughout the pandemic.